On the validity of the Stokes–Einstein relation for various water force fields. (1st June 2020) - Tsimpanogiannis, Ioannis N.; Jamali, Seyed Hossein; Economou, Ioannis G.; Vlugt, Thijs J. H.; Moultos, Othonas A.
Abstract : The translational self-diffusion coefficient and the shear viscosity of water are related by the fractional Stokes–Einstein relation. We report extensive novel molecular dynamics simulations for the self-diffusion coefficient and the shear viscosity of water. The SPC/E and TIP4P/2005 water models are used in the temperature range 220–560 K and at 1 or 1, 000 bar. We compute the fractional exponents t, and s that correspond to the two forms of the fractional Stokes–Einstein relation ( D / T ) ∼ η t and D ∼ ( T / η ) s respectively. We analyse other available experimental and numerical simulation data. In the current analysis two temperature ranges are considered (above or below 274 K) and in both cases deviations from the Stokes–Einstein relation are observed with different values for the fractional exponents obtained for each temperature range. For temperatures above 274 K, both water models perform comparably, while for temperatures below 274 K TIP4P/2005 outperforms SPC/E. This is a direct result of the ability of TIP4P/2005 to predict water densities more accurately and thus predict more accurately the water self-diffusion coefficient and the shear viscosity. GRAPHICAL ABSTRACT: